The concept and essence of reinsurance - Войцеховська, Ірина Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
This article deals with the peculiarities and problems of reinsurance implementation. It examines the main legislative, scientific and theoretical approaches to the definition of «reinsurance» and discloses its legal nature. It’s investigated in the article that nowadays the institute of reinsurance plays a crucial role, to be specific it is an effective mechanism for the protection of property interests of insurers. It allows reinsurers to raise funds while other insurers/reinsurers ensure proper performance of its obligations under the insurance contract and retain the stability of their own financial situation. The author found out that the reinsurance performs a triple role: 1) ensures the financial stability of insurers; 2) protects the interests of insurance consumers from failure or improper performance of insurers of their obligations; 3) protects the state's economics as a whole. However, despite the need for reinsurance, the rapid development of reinsurance market, the emergence of new types of reinsurance services, expansion of geography, it is concluded that in modern legal science there is no comprehensive study of the legal institution. A lot of questions remain unexplored or debatable. The legal framework in the sphere of reinsurance is also developed insufficiently and needs improvement. The main problem, according to the author’s opinion, is that there is no single approach to the definition of "reinsurance" and its legal nature in the modern legal doctrine and its recognition as a subordinate and derivative of insurance. However, as noted in the article, this approach does not meet the legal reality. Although both economic and legal point of view consider reinsurance to be closely related to insurance, but it is not a kind, an area or industry. In particular, the article proves the inadmissibility of equating reinsurance to insurance and distribution of insurance legislation on reinsurance relationship. Reinsurance performs independent functions and has its own importance. And therefore, it requires self-regulation. The article gives the actual definition of the legal institution under which reinsurance is a kind of economic and legal relations on protection of property interests of insurers in the case of certain events (reinsurance events) identified as a reinsurance contract, at the expense of funds formed by insurers paying reinsurance payments (reinsurance premiums, reinsurance contributions) and income from these funds. Also the author proposed to use along with the terms «insurance event», «insurance premium», «insurance payment», «insurance contribution» terms «reinsurance event», «reinsurance premium», «reinsurance payment», «reinsurance contribution».